Students’ conceptions about the formula for a rectangle’s area and some similarities to its historical context - Koleza, Eugenia (NOMAD Nordic Studies in Mathematics Education, 2014)
In this paper, we focus on a debate between grade 6 students about the formula for a rectangle’s area, emerging during a 2-hours teaching, and raising questions about the possibility of using history in order to design a hypothetical learning/teaching trajectory of rectangle’s area, and we analyse students’ conceptions/misconceptions in relation to the historical context of area measurement.